EFEKTIVITAS PUDING BAYAM MERAH (AMARANTHUS TRICOLOR L) TERHADAP PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI - Dewi Sartika Siagian; Desmariyenti Desmariyenti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
According to data Riskesdas (2018) the prevalence of anemia in Indonesian is high, namely 48.9% with the proportion of anemia in the age group 15-24 years and 24-34 years. The dangerof anemia in adolescents, can reduce fitness and concetration causing decreased learining achievement and ability to participate in activities both inside and outside school. Anemia can be treated with non-pharmacological therapy, on of which is red spinach. This study aims to determine the effectiveness of red spinach pudding (amaranthus tricolor l) on increasing hemoglobin levels of anemic adolescent girls at SMP IT Insan Utama Pekanbaru in 2022. This study is a quantitative study using Quasy Experiments. The research design was a One-Group Pretest-Posttest. Population in this study were class IX junior high school students with a total of 17 people at IT Insan Utama Middle School, the sampel taken was 14 people and sampling technique was Consecutive sampling. Data analysis is univariate & bivariate. This study used the Wilcoxon test. The result of the test showed that the effectiveness of red spinach puddings (Amaranthus Trciolos L) had an effect on increasing hemoglobin levels of anemic adolescent girls, which was indicated by the p-value of 0.001 < 0.05, so there was effectiveness. It is suggested to the research site that students know information about the effectiveness of red spinach pudding (Amaranthus Tricolor L) on increasing hemoglobin levels of anemic adolescent girls and can be applied properly to increase hemoglobin levels can be done with non-pharmacological therapy such as comsuming red spinach pudding which can be practically made.Keywords : Red Spinach Pudding, Anemia, Hemoglobin Levels.